PENGEMBANGAN BASIC DIGITAL TRAINER PADA MATA KULIAH RANGKAIAN DIGITAL DI PROGRAM STUDI S1 PENDIDKAN TEKNIK ELEKTRO UNDIKSHA - Didin Agung Gumelar; I Gede Ratnaya; Wayan Mahardika Prasetya Wiratama (Jurnal Pendidikan Teknik Elektro Undiksha, 2021)
This study aims to create the Learning Media Basic Digital Trainer, determine the feasibility of the media, and determine the response of students to the media. This research belongs to the type of R&D (Research and Development). This study uses statistical data analysis of the percentage of eligibility to process data from the content expert test and media expert test, while for the small group test and large group test using the Five Scale Standard model data analysis. This study used a questionnaire as a data collection instrument. The results obtained: media expert validation results obtained a percentage of 98.86% with very decent qualifications, content expert validation results obtained a percentage of 85.41% with very decent qualifications, small group trial results obtained from 5 respondents including the very high category and the results of the large group trial obtained from 21 respondents included in the very high category. Based on the research results, the Learning Media Basic Digital Trainer can be made suitable for use in the learning process in the Digital Circuit course and getting a very good response from students in the Undiksha Electrical Engineering Education S1 Study Program.